Online Home Schooling: Are Parents Ready? Lessons from the Corona Virus Disease Induced Lock Down - Gwendoline Vusumuzi Nani; Lwazi Sibanda (Randwick International of Education and Linguistics Science Journal, 2020)
The outbreak of the corona virus disease (COVID-19) in China around December 2019 led to the premature closure of schools globally. This was done to ensure reduced transmission of the disease. Due to the indefinite level two lockdown in Zimbabwe, schools remain closed. This has led to online home schooling, where schools send work to parents who conduct and monitor the lessons on their behalf. This study sought to find out the experiences and readiness of parents in Bulawayo Metropolitan Province, Zimbabwe, who were expected to conduct lessons online. The study which is situated in the interpretive paradigm and qualitative approach collected data from ten purposively selected parents as key informants. Qualitative data was collected using emailed open-ended questionnaires in compliance with COVID-19 regulations. Results revealed that parents found it difficult to conduct online lessons due to costly data, lack of expert knowledge and teaching pedagogy, unclear instructions from teachers, unavailable or shared gadgets at home and poor internet connectivity. Schools were also said to be piling up work, disregarding parents’ other responsibilities. Conclusions drawn were that most of the parents were not ready for online home schooling although they perceived the exercise to be beneficial. Recommendations were that schools should conduct training sessions for staff and parents, have formal feedback sessions and exercise flexibility for execution and submission of work and continue online lessons post COVID-19. Further research could be conducted to find out learners’ perceptions of online home schooling.